Trust and trustworthiness in corrupted economic environments - Leonardo Becchetti; Luca Corazzini; Vittorio Pelligra (Games, 2021)
We use an original variant of the standard trust game to study the effects of corruption on trust and trustworthiness. In this game, both the trustor and the trustee know that part of the surplus they can generate may be captured by a third "corrupted" player under different expected costs of audit and prosecution. We find a slightly higher trustor's giving in the presence of corruption, matched by a significant excess of reciprocity from the trustee. Both the trustor and the trustee expect, on average, corruption to act as a tax, inelastic to changes in the probability of corruption prosecution. Expectations are correct for the inelasticity assumption and for the actual value of the "corruption tax". Our experimental findings lead to the rejection of four standard hypotheses based on purely self-regarding preferences. We discuss how the apparently paradoxical excess reciprocity effect is consistent with the cultural role of heroes in history, where examples of commendable giving have been used to stimulate emulation of ordinary people. Our results suggest that the excess reciprocity component of the trustee makes the trustor's excess giving a rational and effective strategy.
Keywords: 330; corruption; extended trust game; laboratory experiment